How Social Media Influences Customers’ Purchase Behaviour and Decision Making - Liu, Baiyi (2012)
Since IT’s inception, the internet has become a significant part of people’s normal life, with online sources becoming the most frequent way that people communicate with others and search for information, especially amongst generation Ys (Noble, Haytko and Phillips, 2008).